The Effect of the B-STAD Learning Model on Problem-Solving Ability Reviewed from Self-Regulation Among Elementary School Teacher Education Students - Fanny, Arif Mahya; Sumarmi, Sumarmi; Wardhana, Ery Tri Djatmika Rudijanto Wahju; Sayono, Joko (LJPI UI Bunga Bangsa Cirebon, 2025)
Objective: This study aimed to examine the effectiveness of the B-STAD learning model in enhancing problem-solving ability and to analyze the interaction between learning models and students’ self-regulation. Methods : The study employed a quantitative method with a quasi-experimental design involving 186 Elementary School Teacher Education students who enrolled in 2022. The researchers used problem-solving ability tests and self-regulation questionnaires as instruments, both tested for validity and reliability. The analysis results revealed a significant difference between the group using the B-STAD model and the control group. The average problem-solving ability score for the B-STAD group reached 78.5, while the control group averaged only 65.3. A two-way ANOVA test produced a p-value of < 0.05, indicating that the B-STAD model significantly improved problem-solving ability. Furthermore, the analysis showed that students’ self-regulation had a correlation coefficient of 0.65 with problem-solving ability, demonstrating a strong positive relationship. Results: The findings conclude that implementing the B-STAD model significantly enhances the problem-solving ability of Elementary School Teacher Education students, with an average increase of 13.2 points compared to traditional learning methods. Conclusion: This study recommends that educators consistently apply the B-STAD model in the learning process while also focusing on developing students’ self-regulation. Therefore, this research provides valuable insights into the effectiveness of innovative learning models for improving educational outcomes.